Stakeholder Identified Community Garden Program Outcomes - Susan Webb; John Diaz (EDIS)
Extension clientele often contact agents for expertise on starting or maintaining a community garden; however, agents’ ability to collect meaningful data from these activities can be a challenge. This 3-page publication discusses a statewide study that was conducted by the author to identify community garden outcomes. Written by Susan Webb and John Diaz and published by the UF/IFAS Department of Agricultural Education and Communication, January 2018. http://edis.ifas.ufl.edu/wc295